Anxiety disorders and childhood exposure to emotional abuse: The mediating role of disgust. (13th April 2021) - Innocenti, M.; Santarelli, G.; Gironi, V.; Faggi, V.; Giaquinta, N.; Angeletti, L. Lucherini; Castellini, G.; Ricca, V.
Abstract : Introduction: Several studies demonstrate that disgust, defined as a revulsion response aimed at distancing an individual from a potentially harmful or noxious stimulus, is linked to post-traumatic stress following sexual trauma even when accounting for associated fear and anxiety. One of the suggested mechanisms implicated in this association is a feeling of mental contamination. Recent neuroimaging studies demonstrated that exposure to contamination activates the insular cortex. In addition, disgust sensitivity correlates with the activation of the insular cortex. Objectives: We aimed to investigate the psychopathological role of the emotion of disgust in the developement of anxiety symptoms in patient with an history of abuse. Methods: We enrolled 84 patients admitted in Psychiatric Unit of Careggi with diagnosis of Anxiety Disorders. We administered to them: Zung Anxiety Scale (ZSAS), Childhood Trauma Questionnaire (CTQ), Disgust Propensity and Sensitivity Scale-revised (DPSS-r). Results: Results showed a significant mediation of the association between CTQ emotional abuse scores and total ZSAS scores via DPSS disgust sensitivity scores in patients with anxiety disorders (p=0.022). Total effect and indirect effect of emotional abuse on severity of anxiety symptoms were significant (total effect = 0.494; p=0.051, indirect effect: 0.256, p=0.022), while there was no significant direct effect from emotional abuse to anxiety symptoms in the total model (direct effect: 0.237, p=0.356). The model explained 18% of variance in anxiety symptomatology (R 2 =0.18). Conclusions: Such preliminary data suggest a possible mediating role of disgust in development and maintenance of childhood abuse-related anxiety, making it a potential target for psychotherapy. Disclosure: No significant relationships.